Power Relations and Maritime Justice: An Exploration of UNCLOS Negotiations - Stephanie Oserwa Schandorf (Ocean and Society)
This article offers a novel perspective on the interplay between power relations among states and maritime justice by exploring various manifestations of power during negotiations for the United Nations Convention on the Law of the Sea (UNCLOS). Here, UNCLOS is perceived as an agent of maritime justice insofar as the Convention’s delimitation of maritime zones lays the foundation for establishing the rights and obligations of states in addressing maritime crime and insecurity. It employs Barnett and Duvall’s (2005) taxonomy of power to analyse how key contentions during UNCLOS negotiations were reflective of various forms of power. The discussion reveals that compulsory, institutional, structural, and productive power significantly influenced UNCLOS provisions, often favouring developed states but occasionally benefiting developing nations through collective action. This analysis contributes to a deeper understanding of how power relations among states in the global order can shape the formation of international legal instruments and consequently influence their role as agents of justice.